"The Heidelberg Five" personality dimensions: Genome‐wide associations, polygenic risk for neuroticism, and psychopathology 20 years after assessment. Issue 2 (15th February 2021) - Heilbronner, Urs; Papiol, Sergi; Budde, Monika; Andlauer, Till F. M.; Strohmaier, Jana; Streit, Fabian; Frank, Josef; Degenhardt, Franziska; Heilmann‐Heimbach, Stefanie; Witt, Stephanie H.; Forstner, Andreas J.; Loerbroks, Adrian; et al.
Abstract: HeiDE is a longitudinal population‐based study that started in the 1990s and, at baseline, assessed an array of health‐related personality questionnaires in 5133 individuals. Five latent personality dimensions (The Heidelberg Five) were identified and interpreted as Emotional Lability (ELAB), Lack of Behavioral Control (LBCN), Type A Behavior (TYAB), Locus of Control over Disease (LOCC), and Psychoticism (PSYC). At follow‐up, 3268 HeiDE participants (post‐QC) were genotyped on single nucleotide polymorphism (SNP) arrays. To further characterize The Heidelberg Five, we analyzed genomic underpinnings, their relations to the genetic basis of the Big Five trait Neuroticism, and longitudinal associations with psychiatric symptoms at follow‐up. SNP‐based heritability was significant for ELAB (34%) and LBCN (29%). A genome‐wide association study for each personality dimension was conducted; only the phenotype PSYC yielded a genome‐wide significant finding ( p < 5 × 10 −8, top SNP rs138223660). Gene‐based analyses identified significant findings for ELAB, TYAB, and PSYC. Polygenic risk scores for Neuroticism were only associated with ELAB. Each of The Heidelberg Five was related to depressive symptoms at follow‐up. ELAB, LBCN, and PSYC were also associated with lifetime anxiety symptoms. These results highlight the clinical importance of health‐related personality traits and identify LBCN as a heritable "executive function" personality trait.